Correlation between BCG Immunization Status and The Incidence of Tuberculosis among Children - Annisa Nisa; Ulfa Hamdanah; Anita Dwi Ariyani (Babali Nursing Research, 2020)
Introduction: A children tend to have a high risk on the tuberculosis (TB) infection. BCG immunization is well known as effective way to protect the children from the infection of TB bacteria. Therefore, the study aim was to investigate a correlation between BCG immunization status and the incidence of tuberculosis among children.